Influence of Beauty Micro-Influencer Towards Indonesian Purchase Intention of Skincare Products - Agustinus Krishna Pratama Gracia Adi; Annisa Rahmani Qastharin (Mandalika Journal of Business and Management Studies, 2024)
The Indonesian skincare industry has seen robust growth, with revenue reaching $2.06 billion in 2023 and projected to continue rising. This surge is accompanied by increased market competition, marked by a significant influx of new brands. Consumers face challenges in brand selection, often influenced by social media beauty influencers. This thesis explores the role of micro-influencers in shaping consumer purchase intentions, focusing on their credibility and its impact on brand attitude and purchase behavior. This study the concerning the effectiveness of micro-influencers and sets forth research questions and objectives to evaluate the influence of micro-influencer credibility on brand attitude and purchase intention.The theoretical foundations review relevant literature on influencer marketing, particularly the classification and characteristics of influencers. It delves into the concept of purchase intention and the Ohanian model of credibility, which includes attractiveness, trustworthiness, and expertise. This framework establishes the understanding how micro-influencers affect consumer attitudes and behaviors. The methodology outlines the quantitative approach and survey methodology used to collect data from 160 active skincare users in Indonesia. It details the measurement of variables, such as influencer credibility, brand attitude, and purchase intention, and describes the data analysis techniques using SEM-PLS which is employed to test the hypotheses. Data analysis reveals significant correlations between micro-influencer credibility attributes and brand attitude. Attributes such as expertise, trustworthiness, and attractiveness enhance consumer perception of skincare brands. The analysis confirms that a positive brand attitude mediates the relationship between influencer credibility and purchase intention, highlighting the strategic value of credible micro-influencers in marketing. The thesis concludes that micro-influencers play a crucial role in influencing consumer purchase intentions through their impact on brand attitude. Practical recommendations for skincare brands on leveraging micro-influencer partnerships to enhance market reach and consumer trust and for micro-influencer to focus on enhancing expertiseness and trustworthiness among audience. For future research should explore micro-influencers' impact in different cultures, product categories, long-term brand loyalty, and the effects of post frequency, content type, follower engagement, and emerging social media platforms.